Synthesis and Spectral Characterization of Mixed-Ligand Chelates of Chromium(III) and Manganese(III) with Heterocyclic Thioamide Ligands - Pandey, R.N.; Anand, Abhijeet; Kr. Singh, Rajnish; Kumar, Amaresh (Asian Journal of Chemistry, 2010)
Some trivalent metal chelates of heterocyclic thioamide ligands have been synthesized and characterized by elemental analysis, magnetic, conductance, electronic, infrared and 1H NMR spectral studies. IR spectral data provide unambiguous evidence for the coordination through nitrogen (M-N) and sulphur (M-S) of the ligands. The crystal filed parameters have been calculated and 1H NMR observation are consistent with IR spectral data.